Rantai Pasok Agroindustri Sabut Kelapa pada PT. Berkat Abadi Korindo Kecamatan Matuari Kota Bitung - Olad, Mikha; Lolowang, Tommy Fredy; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the production process of processing, coconut coir  fishing nets and describe the flow of products, information flows and financial flows in the supply chain of fishing nets at PT. Berkat Abadi Korindo, Matuari District, Bitung City. This research was conducted for 2 months from September to October 2022. The sampling method used the purposive sampling method with the purpose and objective of the research, namely by selecting one of the staff/employees at PT. Berkat Abadi Korindo. The research uses primary data obtained from direct observation and interviews with respondents using a questionnaire. The analytical method used in this study is a descriptive analysis with a qualitative and quantitative approach. The results showed that supply chain actors in product flow, information flow and financial flow were farmers, collectors, PT. Berkat Abadi Korindo, expedition services and customers. Product flow in the Jaring Ikan supply chain, namely the supply of raw materials from coconut coir supply farmers to PT. Berkat Abadi Korindo, coconut fiber rope products has been exported to customers using expedition services. The flow of information that flows, namely information about the supply of raw materials from suppliers to factories and then product information from factories to customers. The financial flow that flows is in the form of payments made which pay to suppliers in cash/cash while for customer payments to the factory, namely the transfer payment system.